A Comparative Study between Al-Ri‘āyah by Makkī ibn Abī Ṭālib and Al-Tahdīd by Abū ʿAmr al-Dānī (Journal of the College of Basic Education, 2026)
This research presents a comparative study between Al-Ri‘āyah li- Tajwīd al-Qirā’ah by Makkī ibn Abī Ṭālib (d. 437 AH) and Al-Tahdīd fī al-Itqān wa al-Tajwīd by Abū ʿAmr al-Dānī (d. 444 AH), both of which are prominent works in the science of Qur’anic recitation and tajwīd.The study aims to reveal the methodological approaches of the two authors in dealing with the science of tajwīd, highlighting the points of agreement and difference between them in terms of presentation, analysis, and attention to phonetic and semantic rules. It also seeks to emphasize each author’s contribution to advancing the study of tajwīd and facilitating its understanding for learners.The research adopts the descriptive-analytical method, tracing and classifying the content of both books and comparing them in the arrangement of topics and the methodology of reasoning.The findings indicate that Al-Ri‘āyah li-Tajwīd al-Qirā’ah tends toward detailed explanation and focuses on the practical and instructional aspects of recitation, whereas Al-Tahdīd fī al-Itqān wa al-Tajwīd emphasizes the formulation of general tajwīd principles with scholarly precision and methodological rigor.The study concludes that combining the approaches of both works provides researchers and students with a comprehensive understanding of the science of tajwīd — the former offering detailed pedagogical exposition, and the latter presenting systematic scientific foundations — thereby enriching the field of contemporary phonetic studies